60 international students got the taste of kampung life in Cherok Paloh - UMP, PNC
They came from different countries, practicing different cultures and spoke different languages but it did not deter 60 international students from Universiti Malaysia Pahang (UMP) from having fun and socialising with residents of Kampung Cherok Paloh in Pekan on July 3, 2011.